Liquid chromatography/electrospray ionization tandem mass spectrometry profiling of compounds from the infusion of Byrsonima fagifolia Niedenzu - Sannomiya, Miriam; Santos, Lourdes Campaner dos [UNESP]; Carbone, Virginia; Napolitano, Assunta; Piacente, Sonia; Pizza, Cosimo; Souza-Brito, Alba R. M.; Vilegas, Wagner [UNESP] (Wiley-Blackwell, 2007)
A rapid analytical approach suitable to achieve a comprehensive characterization of the compounds present in the infusion prepared from the leaves of Byrsonima fagifolia Niedenzu (Malpighiaceae), a Brazilian plant used as an infusion to treat gastric disorders, was developed. The method was based on high-performance liquid chromatography coupled to electrospray negative ionisation multistage ion trap mass spectrometry (HPLC/ESI-ITMSn). The main ions in the ESI-ITMS spectra were attributed to a quinic acid core containing from one to five galloyl units. Quercetin derivatives containing one and two sugar moieties as well as galloyl esterification were also detected. These results indicated that HPLC/ESI-ITMSn is easily applicable to infusions of this plant and allows the rapid and direct identification of these compounds in crude plant extracts. Copyright (C) 2007 John Wiley & Sons, Ltd.